The process of inflectional verbal morphology in brazilian portuguese: an eye-tracking study - Justino, Julia Sabrina (2019)
The processing of inflectional verbal morphology has been the subject of an extensive debate in Psycholinguistics. Dual-mechanism theories (Pinker 1998; Ullmanet al.1997) support processing models in which regular verbal forms are processed via rule computation, while irregular verbal forms are retrieved in the memory. On the other hand, single-mechanism theories (Rumelhart & Mcclelland 1986; Stockall & Marantz 2006) claim either regular and irregular inflected forms can be processed by means of a connectionist mechanism or by a process of morphological decomposition. Much of the evidence accumulated so far has been provided by studies of the English past tense (Pinker 1998; Rumelhart & Mcclelland 1986; Stockall & Marantz 2006; Ullmanet al. 1997). Unlike English, the Portuguese language has a complex verbal morphology. In view of the complexity of Portuguese verbal morphological system, a psycholinguistic experiment using the self-paced reading method associated with eye movement recording was conducted aiming at investigating if regular verbs that belong to different verbal classes and tenses are processed in the same or different way. A total of one hundred and eight native speakers of Brazilian Portuguese participated in the experiment. The results suggest that, in the processing of inflected verbal forms, verbal properties like verbal class and tense as well as syntactic elements that are part of the sentence in which the verb is inserted play a role in the processing of verbs.